Simultaneous removal of ammonia nitrogen and sulfide by coupled anammox and sulfur autotrophic denitrification process from industrial wastewater - Jun Li; Salma Tabassum (Cleaner Engineering and Technology, 2022)
This work presents an experimental study on the coupling between anammox and sulfur autotrophic denitrification for simultaneous removal of ammonia nitrogen and sulfide in industrial wastewater, leading to less environmental pollution. In a low-load continuous operation mode hybrid anaerobic baffled reactor (HABR) was started with 7 <pH<8.2 and temperature 30–35 °C. After 60 d of continuous operation successful enrichment of methanogenic granular sludge (MGS) size 7 and 5 mm was achieved. In the mature granular sludge phase (HRT 10 h), with influent chemical oxygen demand (COD) 1100 mg/L, the effluent COD 90 mg/L and removal efficiency was 90%. The MLSS, MLVSS, and f values were 9520, 6980, and 0.7. After 42 d of continuous operation with influent COD 600–700 mg/L, NO3−-N 250-300 mg/L, and COD/NO3−-N 2 to 2.8 (temperature 30–35 °C and pH 6.5–7.5) successful enrichment of denitrifying granular sludge (DGS) was achieved. In the research, the anammox start-up periods in MGS and DGS reactors are 86 and 118 d. An experimental comparative analysis to explore the influence of COD/TN 1:1,1:1.8,1:4.5, and 1:8.5 on the two reactors was performed. For COD/TN 1:1.8, the NH4+-N, NO2−-N, and TN removal efficiency were 54%, 73%, and 52%. The removal efficiency of the #2 reactors NH4+-N, NO2−-N, and TN were 50%, 60%, and 55%. S2−/NO3−-N of 2:5, 3.5:5, 5:5, 6.5:5 were investigated. Influent pH 7.5–8.0, temperature 30–35 °C and HRT 6.5 h, with average influent NH4+-N, NO3−-N, S2−, COD concentration 60, 25, 75, and 25 mg/L, the maximum removal efficiency of #1 reactor was 70%, 97%, 82%, and 100%. For 2# reactor 82%, 99%, 84%, and 100%. When MGS as carrier, the NH4+-N, NO3−-N, and S2− removal efficiency reached 67.67%, 98.59%, and 99.1%. With DGS as carrier, the NH4+-N, NO3−-N, and S2− removal efficiency reached 81.82%, 98.69%, and 84.18%. However, the coupling phase S0 production and productivity results showed that the DGS reactor was significantly better than the MGS reactor. Under the same hydraulic conditions the two reactors successfully coupled after 54 d of operation. Additionally, polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE) analysis, revealed that the microbial community change is related to the concentration of organic matter, nitrogen and sulfur in the water. Building on these findings, future study will focus on the optimization of the mix design to provide practical engineering guidance.